David Beckham : My Side - Beckham, David and Watt, Tom (London CollinsWillow, 2003)
David Beckham is one of the world's foremost media icons, his popularity transcending sport and cultural divides. This is his own in-depth account of his career, for Manchester United and England, and of his childhood, family and personal life.
Include Index and Illustration
Keywords: Beckham, David, 1975- -- Soccer players -- England